Precursors of Openness to Provide Online Counseling: The Role of Future Thinking, Creativity, and Innovative Behavior of Future Online Therapists - Alt, Dorit; Boniel-Nissim, Meyran; Naamati-Schneider, Lior; Meirovich, Adaya (Frontiers in Psychology, 2022)
The outbreak of the COVID-19 pandemic has accelerated the need for online counseling to preserve therapeutic processes that have begun face to face and to provide service to others in need during lockdowns. Previous studies underscored the importance of providing updated training as counselors frequently hesitate to use technological advances in therapeutic sessions. This study aims at reducing such barriers by revealing personal characteristics of future professionals that might inhibit or encourage their openness towards providing online counseling. To this end, this study is focused on several precursors of openness to provide online counseling: preference to communicate emotions online, identification of emotional expressiveness advantages in providing online counseling, innovative behavior, creativity, and future problem-solving thinking skills. The question at focus is which constructs would be found contributive to students’ openness to provide online counseling. The sample included 277 undergraduate students (future counselors) who filled out questionnaires. Data were analyzed using Partial Least Squares Structural Equation Modeling. Our findings pointed to the centrality of students’ preference to communicate their emotions online in explaining their openness to conducting online counseling. This study might help pinpointing the adjustments curriculum designers should address to better reflect the intensive changes within the counseling field that necessitate transferring face-to-face skills to online settings.